APAKAH KONEKSI POLITIK DAPAT MEMPERKUAT FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK? - Yhoga Heru Pratama; Hadri Kusuma ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2022)
The purpose of this study was to examine the effect of Good Corporate Governance, Profitability, Leverage, and Firm Size on Tax Avoidance with Political Connections as a moderating variable. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange during the period 2015 – 2020. The sample of this study was obtained using a purposive sampling method, where only 134 manufacturing companies listed on the Indonesia Stock Exchange met the criteria, so that 804 data were used as samples study. Sources of data obtained from the website of the Indonesia Stock Exchange and the company concerned. This study uses multiple linear regression models to examine the effect of each variable on tax avoidance. Empirical evidence shows that Good Corporate Governance, Profitability, and Leverage have no effect on tax avoidance. While the size of the company has a negative and significant effect on tax avoidance. The political connection moderating variable only moderates the relationship between firm size and tax avoidance.Keywords: Good Corporate Governance, Profitability, Leverage, Company Size, Political Connection